Comparative Analysis of Different Remote Sensing Techniques for Mapping of Supraglacial Lakes on Hispar Glacier - Maha Qaisar; Muhammad Shafiq (International Journal of Economic and Environmental Geology, 2018)
The glacier changes are very significant in quantifying the direct effects of climate change. The glaciers in the northern Pakistan especially in the Karakoram pose a large change in relief and are difficult to access due to complex topography. The global WOS (Web of Science) database indicate only a few studies conducted so far in this region in the domain of climate and cryosphere. The studies relating to glacial hazards in this region are even less. This study involves the mapping of supraglacial lakes on Hispar glacier using multiple remote sensing methods. The accuracy of results from those methods is discussed. Remote Sensing and GIS techniques have been applied to time series of Landsat images of years 2017, 2016, 2010, 2000 and 1990 (in the descending order) to quantify the supraglacial lakes on the Hispar glacier. The remote sensing techniques include Band Rationing, Normalized Water Index (NDWI), Classification i.e. Unsupervised and Panchromatic Sharpening Image Enhancement Technique for the years of 2017 and 2016 imageries. After defining the Hunza basin (involving of high resolution DEMs), all the satellite derived imageries have been preprocessed and processed. GIS tools have been used to calculate the areal extents of yearly obtained supraglacial lakes and compare temporally with passing years, which in turn gave an accurate comparative analysis among different remote sensing techniques. The satellite derived time series map layouts of each technique have been formulated. The vulnerable supraglacial lakes on Hispar glacier of areal sizes ≤ 0.05 sq.km have also been identified and delineated.